Bridging the gaps: a literature review on the integration of creativity in counseling practice - Lisa Putriani (Indonesian Institute for Counseling, Education and Theraphy, 2023)
The integration of creativity into counseling methodologies has garnered significant scholarly attention due to its potential to enhance therapeutic interventions. Nevertheless, this literature review highlights several critical gaps that must be addressed to optimize the efficacy of creative strategies in counseling. The analysis identifies five primary areas of deficiency: limited empirical research on effectiveness, inadequate integration within established counseling theoretical frameworks, a restricted understanding of the underlying mechanisms of change, insufficient attention to cultural and individual variations, and a lack of standardized instruments and training protocols. By examining 18 contemporary sources, the findings underscore the urgent need for extensive longitudinal studies, exploration of creative integration within established counseling theories, comprehensive investigations into mechanisms of change, culturally specific adaptations, and the development of professional training initiatives. This article advocates for future research directions and practical pathways to strengthen the foundation of creativity integration in counseling and improve mental health service outcomes.